Ketogenic diet alleviates renal fibrosis in mice by enhancing fatty acid oxidation through the free fatty acid receptor 3 pathway - Qiu, Yang; Hu, Xiaofan; Xu, Cong; Lu, Chenqi; Cao, Rui; Xie, Yanan; Yang, Jun (Frontiers in Nutrition, 2023)
The ketogenic diet (KD), as a dietary intervention, has gained importance in the treatment of solid organ structural remodeling, but its role in renal fibrosis has not been explored. Male C57BL/6 mice were fed a normal diet or a KD for 6 weeks prior to unilateral ureteral obstruction (UUO), a well-established in vivo model of renal fibrosis in rodents. Seven days after UUO, serum and kidney samples were collected. Serum β-hydroxybutyrate (β-OHB) concentrations and renal fibrosis were assessed. NRK52E cells were treated with TGFβ1, a fibrosis-inducing cytokine, and with or without β-OHB, a ketone body metabolized by KD, to investigate the mechanism underlying renal fibrosis. KD significantly enhanced serum β-OHB levels in mice. Histological analysis revealed that KD alleviated structural destruction and fibrosis in obstructed kidneys and reduced the expression of the fibrosis protein markers α-SMA, Col1a1, and Col3a1. Expression of the rate-limiting enzymes involved in fatty acid oxidation (FAO), Cpt1a and Acox1, significantly decreased after UUO and were upregulated by KD. However, the protective effect of KD was abolished by etomoxir (a Cpt1a inhibitor). Besides, our study observed that KD significantly suppressed UUO-induced macrophage infiltration and the expression of IL-6 in the obstructive kidneys. In NRK52E cells, fibrosis-related signaling was increased by TGFβ1 and reduced by β-OHB. β-OHB treatment restored the impaired expression of Cpt1a. The effect of β-OHB was blocked by siRNA targeting free fatty acid receptor 3 (FFAR3), suggesting that β-OHB might function through the FFAR3-dependent pathway. Our results highlight that KD attenuates UUO-induced renal fibrosis by enhancing FAO via the FFAR3-dependent pathway, which provides a promising dietary therapy for renal fibrosis.